Association of post-treatment positron emission tomography with locoregional control and survival after radiation therapy for squamous cell carcinoma of the vulva. Issue 3 (March 2017) - Rao, Yuan James; Hassanzadeh, Comron; Chundury, Anupama; Hui, Caressa; Siegel, Barry A.; Dehdashti, Farrokh; DeWees, Todd; Mullen, Daniel; Powell, Matthew A.; Mutch, David G.; Schwarz, Julie K.; Grigsby, Perry W.
Abstract: Background/purpose: The aim of this study was to investigate the use of post-treatment F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for vulvar cancer and compare metabolic response to clinical outcomes. Materials/methods: This retrospective study included 21 patients with vulvar squamous cell carcinoma treated with curative-intent radiation between 2007 and 2015. All patients received intensity-modulated radiation treatment (IMRT), a pre-treatment FDG/PET-CT, and a post-treatment FDG-PET/CT performed at a median time of 3 months post-IMRT. Results: Median follow-up time was 28 months. Post-treatment FDG-PET/CT demonstrated no evidence of disease (NED) in 12 patients and residual or progressive disease (PD) in 9. FDG-PET/CT response significantly correlated with biopsy-proven locoregional failure ( p  = 0.02) and was the only significant factor associated with overall survival (OS) ( p  = 0.049). Patients with NED on FDG-PET had a 2-year locoregional control (LRC) of 89% versus 25% for those with PD ( p  < 0.01). Patients with NED on FDG-PET/CT had a 2-year OS of 100% versus 42% for those with PD ( p  = 0.02). FDG-PET/CT evaluation had a sensitivity of 100% and a specificity of 71% for detecting pathologically proven residual disease in patients receiving neoadjuvant or definitive radiation. Conclusion: In this single-institution study of women with vulvar cancer, post-treatment response on FDG-PET/CT was associated with LRC and OS.